Languages of community : the Jewish experience in the Czech lands - Kieval, Hillel J. (University of California Press, 2000)
This volume examines the contours and distinctive features of Jewish experience in Bohemia and Moravia. The book presents the histories and myths as well as demography, biography, culture and politics which show the allegiances and alliances that have molded this experience over 200 years.